FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN INDUSTRI MANUFAKTUR YANG LISTED DI BEI - Ricky Samuel Makinto, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the factors that influence the value of manufacturing industry companies listed on the Indonesia Stock Exchange. This research examines the effect of company growth, capital structure, profitability, and earnings per share on firm value. The sample used in this research is 46 manufacturing companies from a total population of 135 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. The side technique used is purposive sampling using secondary data that can be accessed in the annual financial statements. Data processing is performed using eviews 10.0 software. The results showed that capital structure has a positive effect on firm value, while company growth, profitability, and earnings per share have no influence on firm value